The Coverage of Mental Health by Journalists: towards Trust and Constructive Journalism - Chaparro Domínguez, María de los Ángeles; Díaz-Campo, Jesús; Olivar-Julián, Javier (Journal of Applied Journalism & Media Studies, 2026)
In recent years, mental health has gained prominence in the media as the global prevalence of these disorders continues to rise. This study aims to research the processes of newsgathering and news-making related to mental health by Spanish journalists. It examines how journalists specializing in mental health engage with their sources, how they frame their coverage and the extent to which elements of constructive journalism are featured in their reporting. The analysis draws on theoretical frameworks of trust discourses and models of biocommunicability. Ten in-depth interviews were conducted with experienced specialist journalists covering this topic from various media outlets. The findings reveal that healthcare professionals, patients and their family members are the most frequently consulted sources, all of whom are connected to journalists through relationships of trust. Journalists consider source verification essential, except when consulting high-impact journals or well-known professionals. Unlike general health reporters, journalists specializing in mental health demonstrate a greater trust in official sources and are more likely to frame their coverage with a patient-centred approach. While elements of constructive journalism are present in their reporting, they are not fully developed, particularly in terms of providing greater contextual information and engaging in co-authorship with the public.
Keywords: media representation; news ethics; journalism practice; health journalism; biocommunicability; Spain